The trend and determinants of under-five children stunting and the role of different levels of WASH practices on childhood stunting in Nepal. - Shrestha, SK. (Tufts University. Tisch Library., 2019)
This poster shows that there is a substantial decline in under-five children stunting over past decade in Nepal. However, compared to 2011, the adjusted under-five stunting has increased slightly in 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy